University Student Satisfaction: Online Text Review of Private University in Surabaya - Noerhartati, Endang; Budiharseno, Rianmahardhika Sahid (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
In the contemporary educational landscape, online platforms have become crucial in assessing student satisfaction, which is an essential indicator of educational quality. This study investigates student satisfaction at private universities in Surabaya, Indonesia, through the lens of online text reviews. Utilizing a dataset of 1548 reviews, this research employs a co-occurrence network analysis to identify key factors influencing student perceptions. Our findings reveal that aspects such as campus facilities, quality of education, and economic considerations significantly impact satisfaction levels. The implications of these insights are substantial for institutional strategies aimed at improving student experience and enhancing educational outcomes. The study contributes to the understanding of student satisfaction in a digital era, highlighting the role of online reviews in shaping educational improvement efforts.